Pengolahan Data Akuntansi Pada PT. Buminata Aji Perkasa Menggunakan MYOB Accounting Versi 16 - Dahlia; Endang Puji Astuti; Lia Mazia; Nurlina Sari (Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
In producingfinancial statements requires completeness of information, automatic posting, speed, reliability and accuracy. Financial statements have an important role in measuring the performance of a company. The report made by the bus is used as a reference in making the right decision for the company. Research conducted by the author is at PT. Buminata Aji Perkasa, located in South Jakarta. Currently the company's performance is going well, but in preparingfinancial statements still using a manual accounting system and computerization using Microsoft Excel which takes days. Therefore, utilizing one accounting software, Myob accounting version 16, which is easy to learn and understand by all groups. Thus the software can be used to assist in preparing financial reports for various businesses. Myob Software has several main features, namely: sales, purchases, inventory and other features. The results of this study that Myob Accounting can help improve the quality offinancial information and can also help in the speed, accuracy, convenience, completeness, information offinancial statements at PT. Buminata Aji Perkasa.